Pharmacological and toxicological effects of 6-hydroxy-2-mercaptopurine and 6-thioguanine in in vitro and in vivo models of arthritis - Nordin, Nurul Syuhada (2021)
Rheumatoid arthritis (RA) is a chronic inflammatory and systemic auto-immune disease characterized by symmetrical joint inflammation, destruction of articular cartilage and periarticular tissues leading to loss of joint function and morbidity. The abnormal propagation and activation in many types of immune cells lead to the secretion of the most important pro-inflammatory cytokines mediators such as TNF-α, IL-6, and IL-1 that amplify the inflammation. Current treatment includes non-steroidal anti-inflammatory drugs (NSAIDs), glucocorticoids, disease-modifying anti-rheumatic drugs (DMARDs) and biological agents. However, it has limitations such as poor patient response and risk of toxicity. The thiopurines include 6-mercaptopurine (6-MP), 6-hydroxy-2-mercaptopurine (6H2MP) and 6-thioguanine (6TG) are the immunosuppressive agents used in the treatment of acute lymphoblastic leukaemia, autoimmune disorders and organ transplant recipients. The main objective of this study is to determine the effects of selected thiopurines (6TG and 6H2MP) in phorbol myristate acetate (PMA)-activated rabbit synovial fibroblast cells (HIG-82) and Freund's complete adjuvant (FCA)-activated Sprague Dawley rats. Firstly, the therapeutic effects of thiopurines compounds (6MP, 6TG and 6H2MP) in lipopolysaccharide (LPS)-activated RAW264.7 macrophage and PMA-activated HIG-82 cells were carried out in vitro, with diclofenac was used as a positive control drug. The cytotoxicity and nitric oxide inhibition of thiopurines were performed by using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and Griess assays. 6-thioguanine (6TG) and 6H2MP were chosen to be further investigated for their anti-inflammatory potentials in vitro by using various ELISA kit assays to detect the secretion of prostaglandin E2 (PGE2), pro-inflammatory cytokines tumor necrosis factor-alpha (TNF-α), interleukin 1 beta (IL-1β) and interleukin 6 (IL-6). For in vivo studies, the sub-chronic toxicity effects of 6TG and 6H2MP were also determined by employing an FCA-induced arthritic model on Sprague Dawley rats. The effects on histological alterations, haematological parameters, biochemical markers, arthritis severity, secretion levels of enzymes matrix metalloproteinase 1 (MMP1), matrix metalloproteinase 3 (MMP3), cyclooxygenase-2 (COX-2) and pro-inflammatory cytokines (TNF-α, IL-1β & IL-6) in blood serum were determined. The results of LPS-induced RAW 264.7 macrophages demonstrated that 6H2MP and 6TG were able to suppress the production of NO in vitro. They also suppressed the release of NO, PGE2 and inflammatory cytokines (TNF-α, IL-1β and IL-6) in PMA-activated HIG-82 synovial fibroblast cells. 6TG was more effective in reducing the inflammatory reactions compared to 6H2MP by showings suppression in lower doses compared to 6H2MP in all experiments, except in PGE2. Further results in 28-days rats in vivo study showed that 6TG and 6H2MP by histopathological were prone to show their toxicity in high doses (16 mg/kg) compared to lower doses (4 mg/kg and 8 mg/kg). Both drugs 6TG and 6H2MP decreased the paws volume, and arthritic score and brings the normal mobility of rats. Both compounds also decreased the level of pro-inflammatory cytokines, COX-2 and matrix metalloproteinase enzymes (MMP1 and MMP3). The inhibition of TNF-α, IL-1β and NO is an important mechanism by which 6TG and 6H2MP may affect pain and articular inflammation. Collectively, our findings suggested that both 6TG and 6H2MP could be developed as effective candidates for ameliorating inflammatory-associated complications of autoimmune arthritis, with 6TG showing higher potential to inhibit the inflammation that occurs compared to 6H2MP.